Removing Regulatory Barriers to Competition Kosovo Country Economic Memorandum (Country Economic Memorandum, 2021)
Competition can drive productivity growth in Kosovo, especially in the context of the post-Coronavirus disease 2019 (COVID-19) recovery. As the economy rebuilds, it is key that markets function smoothly, and that anticompetitive firm behavior or government intervention do not constrain the path to recovery. Competitive product markets can help a country recover from economic shocks more quickly. Competition in product markets can also prop-up economic recovery in a more inclusive way for the poorest households. Kosovo has made significant progress towards pro-competition regulation of product markets but there is still significant room for improvement. Although the product market regulation (PMR) indicators are limited in scope and should therefore be considered as an entry point for further analysis, this assessment allows to identify potential constraints to competition and possible policy reforms. Kosovo can increase competition by: (a) eliminating public owned enterprise (POE) - related barriers to competition to ensure a level playing field for private and public operators in markets where they compete, (b) improving the regulatory process and facilitating business registration to boost market entry, and (c) introducing policy reforms in network sectors and professional services to eliminate regulatory barriers to competition and avoid anticompetitive practices